If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(3x + 4) = 2(9 + -6x) Reorder the terms: -5(4 + 3x) = 2(9 + -6x) (4 * -5 + 3x * -5) = 2(9 + -6x) (-20 + -15x) = 2(9 + -6x) -20 + -15x = (9 * 2 + -6x * 2) -20 + -15x = (18 + -12x) Solving -20 + -15x = 18 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -20 + -15x + 12x = 18 + -12x + 12x Combine like terms: -15x + 12x = -3x -20 + -3x = 18 + -12x + 12x Combine like terms: -12x + 12x = 0 -20 + -3x = 18 + 0 -20 + -3x = 18 Add '20' to each side of the equation. -20 + 20 + -3x = 18 + 20 Combine like terms: -20 + 20 = 0 0 + -3x = 18 + 20 -3x = 18 + 20 Combine like terms: 18 + 20 = 38 -3x = 38 Divide each side by '-3'. x = -12.66666667 Simplifying x = -12.66666667
| -36=6X-12Y | | 384628x+298473=2937474 | | 6(5-7n)=72 | | -13-p=-11 | | y=4865x+56743 | | (2x-4)/7=-6x | | y=4865x+1996559th | | b/16=4 | | 11t+4(1-4t)= | | 27=16+n | | 4t-10/5 | | 3n+8=5(n-5)+6 | | b+-17=-31 | | -9*5-4Y=36 | | x^2-2dx-y^2=0 | | 15=n/2 | | -9*3-4Y=36 | | (5x-2)/(5x+2)=(x+2)/(x+4) | | 6(x+2)+20x-4=8(x-2)+8 | | 3*2-6Y=-18 | | 3*4-6Y=-18 | | 0.4x-0.7x-20=1 | | 16(1/2x)^4 | | 5(2m+1)=4m+12 | | (1-8/9)/((1/5)/9+2/9) | | 5x^2-10=2x^2 | | -5(y+6)=-10 | | 28=x+9 | | -45.00+15.00=15 | | 30=4x | | 3x^2-1=10 | | (1/5)/9+2/9 |